Pengembangan media LKS berbasis praktikm untuk meningkatkan minat belajar siswa pada materi ekosistem - Fortuna, Ihza Amalia; Fitri Rizkiyah; Rizqi Nur Rachmawati; Mona Anju Sansena (Jurnal Kajian Pendidikan IPA, 2024)
This research aims to develop a practicum-based Student Worksheet (LKS) media to enhance students' learning interest in ecosystem material. The study employed Research and Development (R&D) methodology using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The development of this media has been validated by material experts, media experts, and subject teachers as validators. The instruments used included expert validation sheets, teacher and student response questionnaires, as well as a learning interest questionnaire administered before and after the use of the LKS. The validation results indicated that the practicum- based LKS media was in the "very feasible" category, with an average expert validation score of 89%. Student responses to the media were categorized as "very positive," and there was an increase in students' learning interest scores after using the LKS, with an average gain score of 0.52 (moderate category). In conclusion, the developed practicum- based LKS media is feasible to use and effective in increasing students' learning interest in ecosystem material. The use of LKS containing practicum activities can serve as an engaging and meaningful learning alternative for junior high school students.